Maltodextrin and dental caries: a literature review - Gabriela REZENDE; Lina Naomi HASHIZUME (Faculdade São Leopoldo Mandic, 2018)
Carbohydrates are largely present in our diet. Sucrose the most commonly consumed carbohydrat and presents a high cariogenic potential. Starch has low cariogenic potential but this effect may be increased if it is consumed in combination with a sucrose-rich diet due to a prolonged retention on tooth surfaces. Maltodextrin is derived from the acid hydrolysis and/or enzymatic hydrolysis of corn starch and it is increasingly present in a variety of industrialized foods such as infant formulas, sports drinks and energy supplements. Yet, its role in the development of dental caries is not clear. The objective of this study was to conduct a literature review of the association between maltodextrin and dental caries. Based on the studies included in this review it can be concluded that maltodextrin has an acidogenic potential lower than sucrose, and that there is a lack of studies about the association between maltodextrin and sucrose and it may not be possible to assess the relationship to dental caries.